Ethical considerations for a comprehensive approach to Nature - Castro Carpio, Augusto (2017)
An approach to Nature-related topics requires a comprehensive view, rethinking the importance of committing to ethical conduct with regards to Nature. To do that, the author explores four themes. First, he reviews the notion of ethics throughout History, referring to the relationship between society and Nature in Aristotle, Descartes, Leibniz and Einstein’s work. Second, the author discusses the concept of life, contrasting the concept of rational or intelligent life with a more ample definition of life. What is the life notion we have in mind when we discuss about alive ecosystems and Nature? Third, taking the traditional anthropocentric view from a critical perspective, the author questions whether it is possible to ensure an ethical relationship with Nature based on such traditional viewpoint. Finally, the author argues that the new paradigms on knowing how to live in the world need to be developed from an inetrdisciplinary perspective, aiming at sustainability.